Prevalence of malaria resistance-associated mutations in Plasmodium falciparum circulating in 2017–2018, Bo, Sierra Leone - Leski, Tomasz A.; Taitt, Chris Rowe; Colston, Sophie M.; Bangura, Umaru; Holtz, Andrew; Yasuda, Chadwick Y.; Reynolds, Nathanael D.; Lahai, Joseph; Lamin, Joseph M.; Baio, Victoria; Ansumana, Rashid; Stenger, David A.; et al. (Frontiers in Microbiology, 2022)
In spite of promising medical, sociological, and engineering strategies and interventions to reduce the burden of disease, malaria remains a source of significant morbidity and mortality, especially among children in sub-Saharan Africa. In particular, progress in the development and administration of chemotherapeutic agents is threatened by evolved resistance to most of the antimalarials currently in use, including artemisinins. This study analyzed the prevalence of mutations associated with antimalarial resistance in Plasmodium falciparum from 95 clinical samples collected from individuals with clinically confirmed malaria at a hospital in Bo, Sierra Leone between May 2017 and December 2018. The combination of polymerase chain reaction amplification and subsequent high throughput DNA sequencing was used to determine the presence of resistance-associated mutations in five P. falciparum genes – pfcrt, pfmdr1, pfdhfr, pfdhps and pfkelch13. The geographic origin of parasites using was tracked based on mitochondrial sequences. Relevant mutations were detected in the pfcrt (22%), pfmdr1 (>58%), pfdhfr (100%) and pfdhps (>80%) genes while no resistance-associated mutations were found in the pfkelch13 gene. Detection of the pfmdr1 NFSND haplotype in 50% of the samples indicated increasing prevalence of strains with elevated tolerance to artemeter + lumefantrine (AL) threatening the combination currently used to treat uncomplicated malaria in Sierra Leone. Presence of very high levels of mutations linked to resistance to antifolates suggests widespread resistance to drug combination used for intermittent preventive treatment during pregnancy. The mitochondrial barcodes were consistent with a West African parasite origin with one exception indicating an isolate imported from East Africa.